2010
DOI: 10.1038/aps.2010.80
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant- and anxiolytic effects of the novel melatonin agonist Neu-P11 in rodent models

Abstract: Aim: To investigate the potential antidepressant and anxiolytic effects of Neu-P11, a novel melatonin agonist, in two models of depression in rats and a model of anxiety in mice. Methods: In the learned helplessness test (LH), Neu-P11 or melatonin (25-100 mg/kg, ip) was administered to rats 2 h before the beginning of the dark phase once a day for 5 days and the number of escape failures and intertrial crossings during the test phase were recorded. In the forced swimming test (FST), rats received a single or r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
33
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 52 publications
4
33
0
1
Order By: Relevance
“…decreased immobility in the FST (Micale et al 2006) as well as single and a 5-day (once a day) administration of the novel melatonin agonist NEU-P11 (25-100 mg/kg i.p.) (Tian et al 2010), but one study showed no effects of chronic (14 days in drinking water) administration of melatonin (4 μg/ml) (Brotto et al 2000). Similarly, results obtained with a single administration of the 5-HT 2C antagonist molecules SB206533 (Cryan and Lucki 2000) or SB242084 (Calcagno et al 2009) showed no effects in the rat FST, while the highly selective ↑ significant increase, ↓ significant decrease, ↔ no changes, : tendency to increase, : tendency to decrease, LMA locomotor activity, NOR novel object recognition task, FST forced swimming test.…”
Section: Effects Of Agomelatine In the Fst And Nor Taskmentioning
confidence: 99%
“…decreased immobility in the FST (Micale et al 2006) as well as single and a 5-day (once a day) administration of the novel melatonin agonist NEU-P11 (25-100 mg/kg i.p.) (Tian et al 2010), but one study showed no effects of chronic (14 days in drinking water) administration of melatonin (4 μg/ml) (Brotto et al 2000). Similarly, results obtained with a single administration of the 5-HT 2C antagonist molecules SB206533 (Cryan and Lucki 2000) or SB242084 (Calcagno et al 2009) showed no effects in the rat FST, while the highly selective ↑ significant increase, ↓ significant decrease, ↔ no changes, : tendency to increase, : tendency to decrease, LMA locomotor activity, NOR novel object recognition task, FST forced swimming test.…”
Section: Effects Of Agomelatine In the Fst And Nor Taskmentioning
confidence: 99%
“…Experimental studies have revealed that melatonin exerts a modest activity in different tests for anxiety in rodents ( (Golombek et al, 1993;Loiseau et al, 2006;Papp et al, 2006, Tian et al, 2010, suggesting a primary role for melatonin receptors in mediating the chronobiotic properties of the hormone.…”
mentioning
confidence: 99%
“…In contrast, acute administration of melatonin in the morning was found to be ineffective in most anxiety tests (Golombek et al, 1993;Loiseau et al, 2006;Millan et al, 2005;Papp et al, 2006). However, agomelatine and the melatonin agonist Neu-P11 exhibited potent anxiolytic effects independent of the timing of administration (Millan et al, 2005;Papp et al, 2006, Tian et al, 2010. Although these new drugs were shown to have slightly weaker effects than the classical anxiolytics diazepam and buspirone (Tian et al, 2010), they do not produce sedation (Papp et al, 2006).…”
mentioning
confidence: 99%
See 2 more Smart Citations